2022
DOI: 10.1021/acsbiomaterials.1c01171
|View full text |Cite
|
Sign up to set email alerts
|

Electroconductive Polythiophene Nanocomposite Fibrous Scaffolds for Enhanced Osteogenic Differentiation via Electrical Stimulation

Abstract: Biophysical cues are key distinguishing characteristics that influence tissue development and regeneration, and significant efforts have been made to alter the cellular behavior by means of cell−substrate interactions and external stimuli. Electrically conductive nanofibers are capable of treating bone defects since they closely mimic the fibrillar architecture of the bone matrix and deliver the endogenous and exogenous electric fields required to direct cell activities. Nevertheless, previous studies on condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Conductive materials are able to conduct bioelectric signals and mimic the micro current environment of bone tissue, but external electric fields are needed, which brings inconvenience to implant applications. [ 23 ] To address these limitations, this study adopted a combined conductive and piezoelectric approach. Specifically, a conductive matrix was used to bridge piezoelectric material, and an integrated piezoelectric/conductive network was established inside the scaffold to facilitate the free flow of charges.…”
Section: Discussionmentioning
confidence: 99%
“…Conductive materials are able to conduct bioelectric signals and mimic the micro current environment of bone tissue, but external electric fields are needed, which brings inconvenience to implant applications. [ 23 ] To address these limitations, this study adopted a combined conductive and piezoelectric approach. Specifically, a conductive matrix was used to bridge piezoelectric material, and an integrated piezoelectric/conductive network was established inside the scaffold to facilitate the free flow of charges.…”
Section: Discussionmentioning
confidence: 99%
“…A hyperbranched aliphatic polyester (HAP)-PTh-PCL scaffold was found to have a Young’s modulus of 59.81 kPa compared to 24.7 kPa for skeletal muscle ( Jaymand et al, 2016 ). Other studies, however, have shown that the addition of PTh into another material caused the mechanical properties (such as the Young’s modulus) to decrease ( Dias et al, 2019 ; Park et al, 2022 ). Although PTh suffers from similar issues as other CPs such as brittleness and reduction in Young’s modulus, these problems have been resolved by the addition of other biomaterials into the scaffold.…”
Section: Biomaterials Used In Skeletal Muscle Regenerationmentioning
confidence: 99%
“…They can be self-assembled by achieving a reversible state transformation and function as needed (Neffe et al, 2021). Stimulus-responsive materials are required to fabricate printed structures in response to external stimuli for shape transformation and functional tuning (Park et al, 2022). According to different types of stimuli, smart materials are divided into physical, chemical, and biological stimulus responsiveness (Figure 1A).…”
Section: Stimulus-responsive Materialsmentioning
confidence: 99%
“…Globally, many reconstructive procedures are required yearly to cope with bone defects caused by accidental fractures, osteoporosis, cancer, and hereditary diseases such as chondromalacia (Sun et al, 2022). Although bone has the intrinsic property of selfrepair, in many cases, bone cannot fully regenerate and requires external stimulation (Chircov et al, 2021;Park et al, 2022), which leads to a very high number of patients with bone defects requiring bone grafts or replacements. Current solutions to address bone defect disorders include medical procedures, grafting, and pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%